Synthesis of Renewable meta‐Xylylenediamine from Biomass‐Derived Furfural. (16th May 2018) - Scodeller, Ivan; Mansouri, Samir; Morvan, Didier; Muller, Eric; de Oliveira Vigier, Karine; Wischert, Raphael; Jérôme, François
Abstract: We report the synthesis of biomass‐derived functionalized aromatic chemicals from furfural, a building block nowadays available in large scale from low‐cost biomass. The scientific strategy relies on a Diels–Alder/aromatization sequence. By controlling the rate of each step, it was possible to produce exclusively the meta aromatic isomer. In particular, through this route, we describe the synthesis of renewably sourced meta ‐xylylenediamine (MXD). Transposition of this work to other furfural‐derived chemicals is also discussed and reveals that functionalized biomass‐derived aromatics (benzaldehyde, benzylamine, etc.) can be potentially produced, according to this route.